Isolated hepatosplenic abscess from cat scratch disease in a patient with HIV. Issue 5 (3rd September 2021) - Buragamadagu, Bhanusowmya; Song, Chen; GuhaRoy, Shambo; Madison, Gul
Abstract: Bartonella henselae infection, or cat scratch disease, typically is a self-limiting disease presenting as lymphadenopathy and fever after a bite or scratch from a cat. The most commonly reported presentation in immunocompromised patients includes bacillary angiomatosis and peliosis hepatitis, which resemble Kaposi's sarcoma. Isolated hepatosplenic abscess without diffuse lymphadenopathy or vasoproliferative disease is seldom reported in adult immunocompromised patients. Although several advances have been made in identifying the organism and antibodies with serological tests, biopsy, and polymerase chain reaction, there is little information about treatment. We report a case of an isolated hepatosplenic abscess without lymphadenopathy or vasoproliferative disease caused by B. henselae in an adult immunocompromised patient with HIV.